Philanthropy as the genesis of Special Education - Lehmkuhl, Márcia de Souza (2021)
The objective of this study is to discuss philanthropy as the genesis of Special Education based on the Associations of Parents and Friends of the Exceptional (Apaes). The Apaes, as institutions for the attendance of people with disabilities, were popularized and disseminated, gradually constituting a true subsystem of Special Education, with an existence of more than two thousand units spread across the country, with state federations and a national federation. As an empirical, field was elected the magazine Mensagem da Apae from the period of 1974 to 2016, totaling 105 issues. To analyze the content of the magazines we sought the contributions of Gramsci (2001; 2014), delimiting categories of analysis, such as Integral State and hegemony. Based on the analysis we divided the historical period in three moments linked to philanthropy: traditional philanthropy, professionalization of philanthropy and the new philanthropy and the “third sector”. It was concluded that the philanthropy accompanies the Special Education since its beginnings, although the philanthropy has undergone changes over time, the mark of disability is what defines aid to the helpless, the charity and the benevolence. The attendance to people diagnosed with intellectual and multiple disabilities in philanthropic private institutions, especially in APAEs, took place with the approval of the State.